Inhibitors of DNA precursor metabolism in Dictyostelium discoideum. - Deering, R A (1982)
The effects of various inhibitors of DNA precursor metabolism were studied on Dictyostelium discoideum growing in a defined axenic medium. Fluorodeoxyuridine was an effective inhibitor of growth at 20 micrograms/ml; this inhibition was not reversed by thymidine, suggesting that in this organism fluorodeoxyuridine is not acting on thymidylate synthetase alone. Removal of the required nutrient, folic acid, from the medium resulted in a lower maximum level of growth than in the control. The inclusion of adenine, guanine, serine, and thymidine in the minus-folic acid medium allowed the final growth level to approach that of the control. Methotrexate, a folic acid analog and dihydrofolate reductase inhibitor, blocked growth completely at 200 micrograms/ml; its effect was partly reversed by the addition of adenine, guanine, serine, and thymidine. Aminopterin, another folic acid analog, had only a temporary effect on cell multiplication, followed by a return to exponential growth. Trimethoprim was ineffective up to 200 micrograms/ml. Hydroxyurea blocked growth in the concentration range of 150 to 300 micrograms/ml. These results indicate that several of these inhibitors are effective for altering thymidine monophosphate synthesis in D. discoideum and hence may be useful for studies of DNA replication and repair and for the isolation and characterization of thymidine-requiring mutants.